2018
DOI: 10.3390/sports6020036
|View full text |Cite
|
Sign up to set email alerts
|

Is a Bimodal Force-Time Curve Related to Countermovement Jump Performance?

Abstract: A countermovement jump (CMJ) represents one of the most frequently used performance tests for monitoring neuromuscular function in athletes. An often-overlooked feature that may provide some useful diagnostic information is the actual shape of the force-time curve. The aim of this study was therefore to consider how the shape of the force-time curve influences jump performance. Thirty-three male rugby union players performed two CMJs on a force plate, with discrete variables and continuous curve analysis used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 43 publications
4
38
3
Order By: Relevance
“…The aforementioned outcomes of the current study contradicted a study by Kennedy et al [21] reporting that the DPC did not represent an optimal pattern of CMJ performance and it could be characterized as an ineffective SSC. The discrepancy could be due to the instruction differences between to "jump as high as possible" [21] and "jump as fast and as high as possible" [22] for the participants. The different instructions could alter the utilized movement strategies [47].…”
Section: Spccontrasting
confidence: 99%
See 4 more Smart Citations
“…The aforementioned outcomes of the current study contradicted a study by Kennedy et al [21] reporting that the DPC did not represent an optimal pattern of CMJ performance and it could be characterized as an ineffective SSC. The discrepancy could be due to the instruction differences between to "jump as high as possible" [21] and "jump as fast and as high as possible" [22] for the participants. The different instructions could alter the utilized movement strategies [47].…”
Section: Spccontrasting
confidence: 99%
“…The instruction may not the only factor causing differences in the DPC and SPC. The outcome found in the DPC with larger hip, knee and ankle flexion angular displacements compared to the SPC in the current study was similar to that of larger braking center of mass displacement in the study by Kennedy et al [21]. The current study suggested that the kinematic features combined with the aforementioned hip, knee and ankle (proximal-to-distal) extensors exertion sequence might cause the GRF signal to depress momentarily and thus provide two distinct peaks inferring the importance of the pattern of multi-joint force application and coordination for a good CMJ performance [17].…”
Section: Spcsupporting
confidence: 90%
See 3 more Smart Citations